Community perceptions and experiences of alcohol-related crime and safety in entertainment precincts. (7th October 2012) - Wiggers, J; Tindall, J; Groombridge, D; Gillham, K; Miller, P; Palmer, D
Abstract : Background: Licensed premises in entertainment precincts are associated with alcohol-related harm, especially violence and anti-social behaviour. Aims/Objectives/Purpose: To determine experiences of alcohol-related crime and perceptions of safety in local entertainment precincts; and whether these varied based on city of residence, proximity of residence to the precinct, visiting the precincts at night, and risky drinking. Methods: A randomised cross-sectional household survey was undertaken in two regional cities (NSW and Victoria, Australia) using telephone surveys in 2010. The data were analysed by frequencies, and differences were analysed with χ 2 and Fishers Exact tests. Results/Outcome: 694 residents participated in the survey (53%). In relation to their local entertainment precinct, 90% thought alcohol was a major issue, 77% thought that alcohol consumed at licensed premises contributed largely to local crime and 84% perceived violence as being the most significant issue relating to intoxicated people. Sixty-eight per cent of respondents wouldn't walk alone after dark, and 76% wouldn't wait for public transport alone after dark. Respondents that had not visited the precinct after dark in the last year were significantly more likely to not walk or wait for transport alone (80% and 86% respectively). Respondents who consumed alcohol at risky levels were less likely to perceive alcohol as being a problem and were more likely to walk or wait for transport alone at night. Significance/Contribution to the Field: The results from this survey provide valuable information on the experiences and perception of crime and safety in regional entertainment precincts.